Host Cell Poly(ADP-ribose) glycohydrolase Is Crucial for Trypanosoma cruzi Infection Cycle - Vilchez Larrea, Salomé Catalina (2013)
Trypanosoma cruzi, etiological agent of Chagas´ disease, has a complex life cycle which involves the invasion of mammalian host cells, differentiation and intracellular replication. Here we report the first insights into the biological role of a poly(ADPribose) glycohydrolase in a trypanosomatid (TcPARG). In silico analysis of the TcPARG gene pointed out the conservation of key residues involved in the catalytic process and, by Western blot, we demonstrated that it is expressed in a life stagedependant manner. Indirect immunofluorescense assays and electron microscopy using an anti-TcPARG antibody showed that this enzyme is localized in the nucleus independently of the presence of DNA damage or cell cycle stage. The addition of poly(ADP-ribose) glycohydrolase inhibitors ADP-HPD (adenosine diphosphate (hydroxymethyl)pyrrolidinediol) or DEA (6,9-diamino-2-ethoxyacridine lactate monohydrate) to the culture media, both at a 1 μM concentration, reduced in vitro epimastigote growth by 35% and 37% respectively, when compared to control cultures. We also showed that ADP-HPD 1 μM can lead to an alteration in the progression of the cell cycle in hydroxyurea synchronized cultures of T. cruzi epimastigotes. Outstandingly, here we demonstrate that the lack of poly(ADP-ribose) glycohydrolase activity in Vero and A549 host cells, achieved by chemical inhibition or iRNA, produces the reduction of the percentage of infected cells as well as the number of amastigotes per cell and trypomastigotes released, leading to a nearly complete abrogation of the infection process. We conclude that both, T. cruzi and the host, poly(ADP-ribose) glycohydrolase activities are important players in the life cycle of Trypanosoma cruzi, emerging as a promising therapeutic target for the treatment of Chagas´ disease.